Sharp Weighted Estimates for a Class of $n$-Dimensional Hardy-Steklov Operators (Communications in Mathematical Research, 2021)
In this paper, we study one class of $n$-dimensional Hardy-Steklov operators which has important applications in the technical analysis in equity markets.We establish their weighted boundedness and the corresponding operator norms onboth $L^p(\boldsymbol{R}^n)$ and BMO($\boldsymbol{R}^n$).
Keywords: Hardy-Littlewood average; Hardy-Steklov operator; BMO.